(untitled) (Dissertare, 2021)
In Venezuela, the Higher Education Student Community Service Law states that community service is an activity that university students must carry out by applying the knowledge acquired during their professional training, for the benefit of society, by linking with communities. This represents a requiremBnt to obtain the respective academic degree. However, the current pandemic by COVID 19 has forced university institutions to carry out these activities in the virtual modality, due to the social distancing measures imposed. Faced with this reality, the following questions arise: Will the work of students who must carry out community service continue to be social, without face-to-face activities in the communities? What are the limitations faced by Venezuelan student community service in the context of the pandemic? The general objective of this essay is to analyze the social dimension of Venezuelan student community service, under the modality of virtual execution during the COVID 19 pandemic. It has a qualitative methodological approach, with documentary design, based on the critical analysis of the subject. It highlights the educational repercussions of the pandemic on community service activity, seriously limited by confinement and social distancing, taking into account the technological gaps that do not favor participation in virtual spaces. It is concluded that without community participation, student community service loses its essence and focus, so actions must be reinforced to reduce morbidity and mortality and to overcome the technological gaps that affect the execution of this socio-educational process.